Toward healthy migration: An exploratory study on the resilience of migrant domestic workers from the Philippines. (August 2014) - van der Ham, Alida Joanna; Ujano-Batangan, Maria Theresa; Ignacio, Raquel; Wolffers, Ivan
Domestic workers face many migration-related stressors that affect their mental health. Currently there is an emphasis in the literature on these workers' problems and vulnerability, while there is little insight into factors that positively affect their mental health. In this study, we describe a range of factors that potentially contribute to the resilience of female domestic workers from the Philippines, and explore their relation to stress and well-being. The study used an explorative, mixed-methods design. First, data were collected using questionnaires ( n = 500) to assess self-perceived stress levels, well-being, personal resources, and social resources. Then, findings from the questionnaires were validated and elaborated on in a workshop ( n = 23) and two focus groups ( n = 13; n = 8). Results show that participants perceived their well-being abroad as relatively good, while they also experienced high levels of stress. Workers used a variety of resources in dealing with stress. Socially oriented coping strategies and spirituality seemed to play an important role as personal resources, while the influence of reasons for migration was less clear. Employers and (access to) social networks appeared important in determining social resources. Social resources were more often related to stress and well-being than were personal resources. Findings from this study can help to design strengths-based interventions aimed at improving the well-being of female domestic workers and preventing mental health problems. The environmental factors and structural constraints that provide the context for resilience should be further explored as they influence the ability to mobilize resources.